Biomethane Production Potential of Sunflower Straws: The Case of Turkey - Uyaver, Mehmet Ugur; Cinar, Deniz; Yoruklu, Hulya Civelek; Ozkaya, Bestami; Demir, Ahmet (Mehmet Sinan Bilgili, 2020)
The annual amount of sunflower stalks, one of the most commonly produced agricultural wastes in Turkey, exceeds 1 million tonnes. The fact that this waste cannot be used in the food industry or as animal feed makes it difficult to manage. However, the use of agricultural wastes in bioenergy production has gained importance in recent years. In this study, the theoretical biomethane production potential of sunflower straws was investigated. As a result of the calculations based on the studies in the literature, the formulation of the sunflower stalk was C45H63O24N and according to this formulation, the amount of biomethane that can be produced from the sunflower straws can reach up to 600 million m(3) of methane.
Keywords: Agricultural waste; Biomethane potential; Sunflower straw; STRUCTURAL FEATURES; BIOMASS; Engineering; Environmental Sciences & Ecology